Advances on neural circuits of paroxysmal kinesigenic dyskinesia - LI Zi⁃yi; FANG Kan; HUANG Xiao⁃jun; CAO Li (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Paroxysmal kinesigenic dyskinesia (PKD) is a kind of nervous system disease characterized by paroxysmal involuntary movements induced by sudden movements. Neuroimaging studies have found that there are structural changes or abnormal functional connectivity in the basal ganglia, thalamus, cortex and other brain regions in PKD patients. The weakened inhibitory and regulatory function of the basal ganglia to the thalamus or the dysfunction of the thalamus itself may cause over⁃activation of the cortical region, resulting in involuntary movements. Recent studies have found that abnormal cerebellar function plays an important role in the pathogenesis of PKD, and abnormal cerebellar cortex can affect its normal inhibitory effect on deep cerebellar nuclei, also leading to excessive activation of thalamic⁃cortical pathway. This paper reviewed the mechanism and research progress of PKD in recent years, mainly focusing on the basal ganglia⁃thalamic⁃cortical circuit and the cerebellar⁃thalamic⁃cortical circuit, so as to improve clinicians' understanding of the pathogenesis of movement disorders.